What did the European Liver Transplant Registry bring to liver transplantation?. (14th September 2020) - Lerut, Jan; Karam, Vincent; Cailliez, Valérie; Bismuth, Henri; Polak, Wojciech G.; Gunson, Bridget; Adam, Rene
Summary: Since its foundation in 1985, the European Liver Transplant Registry has evolved to become an important tool to monitor the liver transplantation activity in Europe. The vast amount of data collected on 169 473 liver transplantations performed in 153 238 recipients has also resulted in scientific publications. Without doubt, several of these have influenced the daily practice of liver transplantation. This paper gives an overview of the development, the functioning, and the scientific activity of the European Liver Transplant Registry during more than three decades. Indeed, it can be said that the registry helped to advance the practice of liver transplantation not only in Europe but also worldwide.